Quality Estimation of Dry Grinding of Skiving Cutters With Organic Bonding Diamond Wheels; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Filippov A. V. Andrey Vladimirovich; Shamarin N. N. Nikolay Nikolaevich; Podgornykh O. A. Oleg Anatolievich; Rubtsov V. E. Valery Evgenjevich (2016, 2016)
Title screen